Evaluasi implementasi model pembelajaran blended learning pada masa pandemi di kelas I sekolah dasar - Rahmawati, Anita; Marmoah, Sri; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2022)
Education has been severely impacted by the COVID-19 virus that has spread to Indonesia. Learning must be changed from face-to-face learning to online learning to prevent the spread of the COVID-19 virus. The blended learning model is expected to be an effective solution to overcome learning limitations during the pandemic by implementing learning that can penetrate space and time. The implementation of the blended learning model is carried out through limited face-to-face and online learning through Whatsapp media. This study aims to determine the evaluation and assessment of the implementation of the blended learning model in learning. The approach applied in this research is qualitative, with a case study method conducted by exploring the discovery of a problem in the research. The research results were obtained through observation, interview, and documentation data collection techniques. The research data was obtained through the research subjects, which included the principal, first grade teacher, and 5 first grade students. Learning evaluation with a blended learning model based on the research results obtained has been implemented well. Evaluation in its implementation is accompanied by taking scores by teachers and principals. The implementation of the evaluation experienced some obstacles, especially in online learning, but it can be overcome well by using the special skills possessed by the grade I teacher.